Ethno Literacy-Based Early Childhood Articulation Intervention through Unplugged Coding Maze Media - Naili Sakinatina; Irfai Fathurohman; Wawan Shokib Rondli (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
Speech sound disorders (SSD) in early childhood hinder communicative and social aspects. Conventional, repetitive teaching methods often fail because they ignore the cultural context and emotional involvement of children. This approach places ethno literacy as the main framework of intervention which is operationalized through the unplugged coding maze media in stimulating articulation. The research used a descriptive qualitative approach with a case study design on seven children aged 4-5 years with mild SSD criteria at TK Muslimat NU Nawa Kartika, Kudus Regency. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model with triangulation of sources and techniques and member checking. The results of the study showed an average increase in phoneme accuracy of 30.5%. Within the framework of ethno literacy, the use of cultural narratives operationalized through the unplugged coding maze media has been proven to reduce speaking anxiety and increase children's intrinsic motivation. In contrast to conventional speech therapy methods that emphasize repetition exercises, this approach integrates computational thinking and culturally based neurolinguistic stimulation, thereby accelerating the phonological encoding process. The novelty of this research lies in the use of ethno literacy as the main framework of intervention, with unplugged coding maze as a mediation medium in stimulating early childhood articulation. These findings provide implications in the form of a holistic and contextual language intervention model for early childhood educators.